Magnetism in bimetallic NiII-CoII coordination polymer - Gupta, Kriti; Dadwal, Arun; Joy, Pattayil; Ballav, Nirmalya (AIP Conference Proceedings, 2020)
Co-BDC ([Co2(OH)2BDC], H2BDC = 1,4-benzenedicarboxylic acid) is known to possess metamagnetism originating from the antiparallel spins and high magneto crystalline anisotropy of Co(II).1 Herein, we have introduced a bimetallic concept by incorporating Ni(II) along with Co(II) in the same coordination polymer to modulate the magneto crystalline anisotropy in the lattice which in turn, affects the overall magnetic response of the coordination polymer. The Curie-Weiss equation fit suggested antiparallel arrangement of the spins (θ ≈ -62.5 K) of Ni(II) and Co(II) arranged in alternate fashion. The cusp in magnetization was observed at 7 K (Tc) with a significant coercive field of ∼750 Oe at 5 K.